2010
DOI: 10.1080/15567030903078061
|View full text |Cite
|
Sign up to set email alerts
|

The Investigation of Performance and Emissions Characteristics of Tall Oil Biodiesel With a Co-based Additive

Abstract: In this study, the effects of tall oil biodiesel with cobalt (Co)-based additive on engine performance and exhaust emissions have been experimentally investigated. Co-based additive at the rate of 4, 8, and 12 mol/l was added to mixtures of 60% tall oil methyl ester and 40% diesel fuel (T60). The engine tests were performed at full load condition in a single-cylinder diesel engine. Biodiesel fuels had no noteworthy influence on engine torque and the power output values. Catalyst effects of Cobased additive imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Biodiesel can be used as a blending component or a direct replacement for diesel fuel in internal combustion engines (Demirbaş, 2009). In contrast to petrodiesel, the advantages of biodiesel are lower emission of CO due to a better combustion, a better lubricating effect on engines, nonsulfur emission, non-flammable, non-explosive with a flash point of 423 K for biodiesel as compared to 337 K for petrodiesel, portability, ready availability, renewability, higher combustion efficiency, lower sulfur, higher cetane number, higher biodegradability, and non-aromatic content (Phan and Phan, 2009;Meng et al, 2008;Keskin et al, 2010;Balbasi et al, 2011;Basha et al, 2009). Another and important advantage of biodiesel is its domestic origin that would help a country's dependency on imported petroleum (Keskin et al, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…Biodiesel can be used as a blending component or a direct replacement for diesel fuel in internal combustion engines (Demirbaş, 2009). In contrast to petrodiesel, the advantages of biodiesel are lower emission of CO due to a better combustion, a better lubricating effect on engines, nonsulfur emission, non-flammable, non-explosive with a flash point of 423 K for biodiesel as compared to 337 K for petrodiesel, portability, ready availability, renewability, higher combustion efficiency, lower sulfur, higher cetane number, higher biodegradability, and non-aromatic content (Phan and Phan, 2009;Meng et al, 2008;Keskin et al, 2010;Balbasi et al, 2011;Basha et al, 2009). Another and important advantage of biodiesel is its domestic origin that would help a country's dependency on imported petroleum (Keskin et al, 2008).…”
Section: Introductionmentioning
confidence: 98%
“…Figure illustrates that, if nano additive of 100 ppm was doped with B5 blend, then smoke emission was further decreased by 4.76% compared to B5 blend and 7.77% lesser than diesel at 3.7 kW. For the reasons that of the reduced soot formation, secondary atomization effects …”
Section: Resultsmentioning
confidence: 98%
“…KESKIN et al [20] mentioned that the addition of tall oil with cobalt based additive resulted in increased CO emissions, and smoke emissions also higher NOx emissions were measured at low engine speed. AHMED I. EL-SEESYA et al [12] have studied the Influence of Multi-Walled Carbon Nanotubes Additives into Non-Edible Biodiesel-Diesel Fuel Blend on Diesel Engine.…”
Section: Discussion On Emission Parameter With Usage Of Nano Addmentioning
confidence: 99%
“…At the full load, the brake thermal efficiency for the JME fuel observed was 24.80%, whereas it was 26.34% and28.45% for the JME2S5W and JME2S5W100CNT fuels respectively. HARISH VENU et al [19] have found the influence of Alumina (Al2O3) nanoparticle on various injections [20] have found the performance, combustion and emission characteristics of a variable compression ratio engine using Cerium Oxide Nanoparticles and Carbon Nanotubes as fuel-borne nanoparticles additives in Diesterol (diesel-biodiesel-ethanol) blends. The addition of CERIA and CNT in Diesterol blend increases the cylinder gas pressure when comparing with the neat Diesterol blends.…”
Section: Discussion On Emission Parameter With Usage Of Nano Addmentioning
confidence: 99%